Terminals and Connector Inspection Innovation using Machine Vision - Herlambang, Hendi; Humiras Hardi Purba; Zulfa Fitri Ikatrinasari; Kosasih (Prosiding Seminar Nasional Waluyo Jatmiko, 2023)
Customer demands for product quality that are increasingly complex and require more accurate inspection are not sufficient if done manually due to high costs and different operator precision. To solve this problem, automatic vision inspection was created to check the product quality of terminal-type electronic components. Machine Vision is robust equipment for examining electrical components, agroindustry, surface mounting technology industry, plastic industry, and glass industry. In this research, the design and application of machine vision are used to inspect terminals and connectors, supporting automotive and electrical equipment components. Machine vision checks three quality functions, namely structural quality, surface quality, and dimensional quality. Optimization of image capture using backlighting and darkfield lighting. Implementing machine vision is carried out by verifying image retrieval's stability using a gage study with the results that there is no measurement bias.